Design and cohort characteristics of TRACK, a prospective study of hyperkalaemia management decision-making - Hsia, Judith; Shivappa, Nitin; Bakhai, Ameet; Bover, Jordi; Butler, Javed; Ferraro, Pietro Manuel; Fried, Linda; Schneider, Markus; Tangri, Navdeep; Winkelmayer, Wolfgang C.; Bishop, Meredith; Chen, Hungta; et al. (Clinical Kidney Journal, 2024)
Background. Guideline-recommended hyperkalaemia management includes dietary potassium (K+) restriction, bicarbonate correction, diuretics and K+ binders with dose reduction of renin–angiotensin–aldosterone system inhibitors as a last resort. The extent to which these recommendations are implemented is uncertain, as real-world data on hyperkalaemia management are limited. The Tracking Treatment Pathways in Adult Patients with Hyperkalemia (TRACK) study is a multinational, prospective, longitudinal study that is being conducted to address this knowledge gap. We report the design and baseline cohort characteristics of this real-world study of hyperkalaemia management decision-making. Methods. This study enrolled participants within 21 days of an episode of hyperkalaemia in four European countries (UK, Spain, Germany, Italy) and the USA. During the 12-month follow up, data collected will include participant and healthcare provider characteristics (specialty and practice setting), hyperkalaemia treatment objectives and strategies, rationale for management decisions and indicators of response and patient-reported perceptions of their hyperkalaemia treatment. Results. The enrolled cohort includes 1330 participants, mean age 68 years, of whom 31% were women. At baseline, 6% reported heart failure, 55% chronic kidney disease, 29% both and 9% neither. Most participants (57%) were taking an angiotensin-converting enzyme inhibitor, angiotensin receptor blocker or angiotensin receptor/neprilysin inhibitor at baseline. Mineralocorticoid receptor antagonist use was lower (14%). Conclusions. The prospective TRACK study will shed light on practitioners’ hyperkalaemia management decision-making and assess the impact of their decisions on hyperkalaemia recurrence. Understanding practitioners’ underlying thought processes will facilitate efforts to improve hyperkalaemia management. ClinicalTrials.gov: NCT05408039
CRIS-Team Scopus Importer:2024-11-08
Keywords: chronic kidney disease; heart failure; hyperkalaemia management; RAASi; real-world evidence